1982
DOI: 10.1073/pnas.79.7.2273
|View full text |Cite
|
Sign up to set email alerts
|

Intermembrane contact affects calcium binding to phospholipid vesicles.

Abstract: Binding of Ca2+ to liposomes composed of phosphatidylserine (PtdSer) was analyzed by potentiometric titrations. Ca2+ binding to large unilamellar PtdSer vesicles was saturable at a stoichiometry of 1:2 (Ca2+/PtdSer). At approximately 6 X 10(-4) M [Ca2+]free, the binding curve exhibited a discontinuity that can be attributed to the formation of a Ca2+/PtdSer complex with a higher affinity. When both Ca2+ and Mg2+ are present, depending on the relative concentrations, Mg2+ can either complete or can enhance Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 39 publications
5
41
1
Order By: Relevance
“…Also, our results disagree with stability and binding studies (53)(54)(55) that suggested that specific binding occurs between Ca 2þ and the phosphate portion of the PL. Perhaps the relative instability and heterogeneity (in size and possibly composition) of the liposome preparations and the different solvent conditions used (specifically the Ca 2þ concentrations) contribute to these differences.…”
Section: Interactions Of Lipid Nanodiscs With Cacontrasting
confidence: 56%
“…Also, our results disagree with stability and binding studies (53)(54)(55) that suggested that specific binding occurs between Ca 2þ and the phosphate portion of the PL. Perhaps the relative instability and heterogeneity (in size and possibly composition) of the liposome preparations and the different solvent conditions used (specifically the Ca 2þ concentrations) contribute to these differences.…”
Section: Interactions Of Lipid Nanodiscs With Cacontrasting
confidence: 56%
“…Consequently, the surface dielectric constant reduced to lower values, as low as 4. These results suggest that when these strong fusogenic ions interact with acidic lipid membranes, they may form nearly anhydrous complexes of cation and lipid polar groups [5]. They may form a Ca2+-interbridged lipid complex [6,7].…”
Section: Discussionmentioning
confidence: 97%
“…When calcium is present, it is partially bound to PS in the membrane, contributing to the charge stabilization of the membrane; however, a decrease of calcium can perturb the biophysical properties of the membrane and producing its destabilization. It has been shown that sodium binding to PS produces dehydration of the membrane, and, finally, disruption of the membrane integrity (Ekerdt and Papahadjopoulos, 1982). Therefore, it is feasible that one response of the root cells to high salinity concentrations would be the increase of the PS level in the membrane, to achieve more calcium binding to the surface of the membrane, thus contributing to its stabilization.…”
Section: Discussionmentioning
confidence: 99%